High-Speed Microscopy of Diffusion in Pore-Spanning Lipid Membranes - Spindler, Susann; Sibold, Jeremias; Mahmoodabadi, Reza Gholami; Steinem, Claudia; Sandoghdar, Vahid (Nano Letters, 2018)
Pore-spanning membranes (PSMs) provide a highly attractive model system for investigating fundamental processes in lipid bilayers. We measure and compare lipid diffusion in the supported and suspended regions of PSMs prepared on a microfabricated porous substrate. Although some properties of the suspended regions in PSMs have been characterized using fluorescence studies, it has not been possible to examine the mobility of membrane components on the supported membrane parts. Here, we resolve this issue by employing interferometric scattering microscopy (iSCAT). We study the location-dependent diffusion of DOPE 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine) lipids (DOPE) labeled with gold nanoparticles in (1,2-dioleoyl-sn-glycero-3-phosphocholine) (DOPC) bilayers prepared on holey silicon nitride substrates that were either (i) oxygen-plasma-treated or (ii) functionalized with gold and 6-mercapto-1-hexanol. For both substrate treatments, diffusion in regions suspended on pores with diameters of 5 μm is found to be free. In the case of functionalization with gold and 6-mercapto-1-hexanol, similar diffusion coefficients are obtained for both the suspended and the supported regions, whereas for oxygen-plasma-treated surfaces, diffusion is almost 4 times slower in the supported parts of the membranes. We attribute this reduced diffusion on the supported parts in the case of oxygen-plasma-treated surfaces to larger membrane-substrate interactions, which lead to a higher membrane tension in the freestanding membrane parts. Furthermore, we find clear indications for a decrease of the diffusion constant in the freestanding regions away from the pore center. We provide a detailed characterization of the diffusion behavior in these membrane systems and discuss future directions.
CRIS-Team Scopus Importer:2023-03-27
Keywords: interferometric scattering microscopy; lipid diffusion; model membrane system; Pore-spanning membrane; single-particle tracking